A interdisciplinaridade no ensino da matemática: problemas matemáticos oriundos do estudo do sistema solar - Godoi, Maycon Cristian [UNIFESP] (2018)
In this work we bring as a theme “The interdisciplinarity in mathematics teaching: mathematical problems arising from the study of the Solar system”, where we propose the study of how interdisciplinary themes can enrich a class of Mathematics, raising issues such as “contextualization of teaching” and “historical development ”, making use of current technologies and creating dynamic models for lessons from the perspective of Seymour Papert. It will be done a case study of how it is possible to develop mathematics through astronomy, recreating historical problems that have leveraged both sciences.